Pragmatism, identity, and the state; How the Nuaulu of Seram have reinvented their beliefs and practices as "religion" - Ellen, Roy (Wacana, Journal of the Humanities of Indonesia, 2014)
The Dutch colonial state categorized animists and ancestor-worshippers and inscribed them into written records in ways that have had long-term effects. The immediate post-independence period in Maluku, despite early political turmoil, settled down to a kind of stability under the New Order, the paradoxical outcome of which was both gradual integration of Nuaulu into a wider political and cultural consensus and conditions favouring economic change that undermined that consensus. The new policies of reformasi after 1998 presented further opportunities for Nuaulu to engage with the state in ways that promoted their interests. The opportunities were short-lived, however, given the implosive events of the communal unrest that lasted until 2001. This paper illustrates how this history has influenced Nuaulu self-perceptions and conceptualization of themselves as a separate people with a "religion" that goes beyond simply adherence to adat, and how this process has been partly driven by demography and a desire for pragmatic accommodation.